Sakhewa Silli in Bantawa Rai: A Study of Indigenous Ecocriticism - Rai, Man Kumar (JODEM: Journal of Language and Literature, 2025)
This study examines the profound interconnection between the Sakhewa sillis (different steps of cultural dance of Bantawa Rai sub-group of Kirant Rai community) and nature, through the lens of indigenous ecocriticism. Sakhewa dance is not merely a medium of entertainment; its various sillis (dance movements) narrate the Kirant Rai community’s deep relationship with nature, their worldview, and their civilization. Each sillis symbolizes a respectful engagement with the environment, reflecting themes such as agricultural cycles, migration of animals, and spiritual communication with nature and ancestral spirits. The Worldview of the indigenous Kirant Rai community towards nature is depicted through the Sakhewa sillis. However, the influence of globalization and pop culture, historical knowledge are being under shadowed. Many urban youths perceive Sakhewa merely as medium of entertainment. Indigenous ecocriticism has been used as a theoretical tool to reveal ecological consciousness and cultural identity. By highlighting different symbolic meanings of sillis, this paper emphasizes the urgent need to preserve such indigenous cultural expressions as vital forms of environmental and cultural awareness.